Implementation of Nggahi Rawi Pahu Philosophy Through in Chemistry Learning Based on Social Cognitive Theory for Student Character Strengthening - Annafi, Nurfidianty; Admyana, Putu Budi; Suastra, I Wayan; Sutajaya, I Made; Tika, I Nyoman; Wesnawa, I Gede Astra (Universitas Pendidikan Mandalika, 2024)
Social cognitive theory developed by Albert Bandura is the most influential approach to learning. This theory emphasizes that a person's behavior can be learned through observation of social models in the surrounding environment, be it teachers, parents, or peers. This theory is known as observational learning or modeling. This research aims to explore the process of observational learning in an effort to strengthen the value of the Nggahi Rawi Pahu philosophy. The research method used is descriptive qualitative. The sample in this study were fourth semester students of the Chemistry Education Study Program. Data collection techniques were carried out by means of observation, administration of questionnaires and documentation. In this study, observational learning was carried out through 4 stages of cognition in the learning process, namely attention, retention, motor reproduction and motivation. 7 out of 10 students showed a positive response to the relevance, involvement and benefits of observational learning in an effort to strengthen the philosophy of Nggahi Rawi Pahu. This shows that through observational learning the value of the Nggahi Rawi Pahu philosophy can be improved.